Peran Sistem Informasi Akuntansi Manajemen dalam Pengambilan Keputusan pada Perusahaan Digital: Kajian Literatur dan Studi Kasus Tokopedia & Facebook - Susanti, Wanda; Lubis, Sri Rahmi; Firdaus, Rayyan (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2025)
Digital companies operate in environments marked by high uncertainty, rapid technological change, and increasingly demanding consumer expectations. In this context, management accounting information systems (MAIS) serve as vital instruments for delivering relevant, accurate, and timely information to support managerial decision-making. This study aims to analyze the role of MAIS in managerial decision-making within digital companies, using a literature review approach and case studies of Tokopedia and Facebook (Meta). The findings reveal that MAIS contributes not only to operational efficiency but also to strengthening information governance and ethical digital decision-making. This study offers a conceptual contribution by integrating managerial, accounting, and digital responsibility perspectives within the decision-making framework of digital enterprises